Correction: 2, 5-Furandicarboxylic acid as a linker for lanthanide coordination polymers: the role of heteroaromatic π–π stacking and hydrogen bonding. (29th January 2019) - Kumar, Manesh; Nawaz Sheikh, Haq; Franconetti, Antonio; Zaręba, Jan K.; Sahoo, Subash Chandra; Frontera, Antonio
Abstract : Correction for '2, 5-Furandicarboxylic acid as a linker for lanthanide coordination polymers: the role of heteroaromatic π–π stacking and hydrogen bonding' by Manesh Kumar et al., New J. Chem., 2019, DOI: ;10.1039/c8nj05701j .